Differential Impact of Revenues from Natural Resources on Global Public Debt: A Quantile Regression Approach - Ruiz, Yomara (2025)
The relationship between public debt and natural resource rents is a topic of growing relevance in the global economy. In many countries, the exploitation of natural resources is not only an important source of revenue but can also significantly influence the dynamics of public debt. Therefore, this study aims to examine the relationship between natural resource rents and public debt at the global level and across different groups of countries classified by income level during the period 1995-2022. To this end, second-generation econometric techniques that account for cross-sectional dependence among the countries analyzed were employed, revealing both dependence and long-run cointegration among the model variables. Furthermore, quantile regressions show that natural resource rents and economic growth contribute to reducing public debt, whereas technology and unemployment tend to increase it. Only inequality exhibits heterogeneous effects depending on the level of development: it reduces public debt in developed countries but increases it in developing ones. Finally, this study outlines several policy implications for achieving a balanced level of public debt, highlighting the importance of efficient management of natural resource revenues and strategic investment in sectors that foster sustainable economic growth.